Necesidad imperante de que se suprima del Reglamento general a la ley orgánica del servicio Público el artículo 108, primer imnumerado por Cuanto viola claras y expresas normas Constitucionales y legales - Conza Jaramillo, Luis Eduardo (2014)
State policies led by the economist Rafael Correa primarily towards sector workers and public sector workers today show a regression in labor guarantees established in the Constitution and the international conventions of the International Labour Organization ILO right to Organize, Collective Bargaining, the right to strike and even the reproductive rights of women workers. These actions have been implemented from the Ministry of Labor in coordination with the national police and the national army more than show the character overbearing, authoritarian and repressive regime pretending to frighten current, demobilize all the servants of the public sector to once discourage union involvement of other workers who have not been dismissed, mainly young people who have not had an experience in the battles to defend workers' labor rights, a situation exacerbated by failures against and workers by the relevant agencies Constitutional Court, Labour Courts as a result of the control exercised by the president. It is public knowledge that these anti-worker actions, employer pro running have been applied in various Public Sector Institutions both servers, professional and administrative staff. They have not respected the due process rights established in the Constitution of the Republic of Ecuador in order to comply at least with the formalities set out to run a recall system is to the term covered in the provisions CRE and LOSEP.